2000
DOI: 10.1054/bjoc.2000.1550
|View full text |Cite
|
Sign up to set email alerts
|

Childhood cancer and residential proximity to power lines

Abstract: In the United Kingdom Childhood Cancer Study, a population-based case–control study covering the whole of England, Scotland and Wales, measured power-frequency magnetic fields were not found to be associated with risk for any malignancy. To examine further the risk associated with residential proximity to electricity supply equipment, distances to high-voltage lines, underground cables, substations and distribution circuits were collected for 3380 cases and 3390 controls. Magnetic field exposure from this equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…The United Kingdom Childhood Cancer Study ( UK Childhood Cancer Study Investigators, 2000b ) reported a smaller study of childhood leukaemias and other cancers across England, Wales and Scotland, which both measured magnetic fields within the home from all sources and calculated distances to powerlines. It also reported elevated risks for leukaemia that were not statistically significant, though they were compatible with the pooled analyses for magnetic fields and with the Draper et al (2005) results for powerline proximity ( UK Childhood Cancer Study Investigators, 1999 , 2000a ; Draper et al , 2005 ).…”
supporting
confidence: 68%
“…The United Kingdom Childhood Cancer Study ( UK Childhood Cancer Study Investigators, 2000b ) reported a smaller study of childhood leukaemias and other cancers across England, Wales and Scotland, which both measured magnetic fields within the home from all sources and calculated distances to powerlines. It also reported elevated risks for leukaemia that were not statistically significant, though they were compatible with the pooled analyses for magnetic fields and with the Draper et al (2005) results for powerline proximity ( UK Childhood Cancer Study Investigators, 1999 , 2000a ; Draper et al , 2005 ).…”
supporting
confidence: 68%
“…The UK Childhood Cancer Study (UKCCS) calculated magnetic fields from measured currents in overhead power lines with voltages ranging from 11 to 400 kV, for the home addresses of 6770 children in Britain during 1991–1996 (3380 cases of childhood cancer and 3390 controls) ( UK Childhood Cancer Study Investigators, 2000a ). The geographical areas and time periods overlap with those for our study, and the same computer programme was used for the field calculations, but the overall proportion of addresses with fields above 0.1 μ T is higher in the UKCCS (0.52%) than in our study (0.07%).…”
Section: Discussionmentioning
confidence: 99%
“…We identified 21 studies on distance to power lines published between 1993 and 2016, of which 13 met our inclusion criteria (Table 1) 14,15,1719,4451 . Eight studies were excluded; reasons for their exclusion are provided in the appendix (Table S1) 52–59 .…”
Section: Methodsmentioning
confidence: 99%